UPAYA PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA BUDDHA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE SISWA MIDDLE YEARS PROGRAMME DI MEDAN INDEPENDENT SCHOOL - ERICA WINATA PHENJAYA (JURNAL PROINTEGRITA, 2018)
The aim of this research is to improve the students’ learning outcomes on Budhist subject by applying the Cooperative learning model type Think Pair Share (TPS). The TPS is one of the learning model type that suppose to encourage the students’ interaction and communication in learning process. Thus, in the first cycle the teacher gives reading papers to be read and understood by students before the teacher explains the material. Then the teacher gives the students questions to answer in the answer sheet provided. Then the teacher instructed students to group and discuss, and continued with the presentation of each group in front of the class. In the second cycle there is a difference which gives the paper a teacher after reading, explaining the material by using power point accompanied by a video. In learning activities, the majority of students are more enthusiastic and ask questions to the teacher. Some of them even argued about students' understanding regarding the material. Furthermore, for each process the same as in cycle I. Based on the results of the implementation of the cooperative learning model type Think Pair Share (TPS) can improve the learning outcomes of Buddhist studies in Middle Years Program students at Medan Independent School. The results in cycle I obtained an average value of 70.70. Classically students who reach the percentage of student learning outcomes are 37.50% which reaches a value of > 75 according to the minimum completeness criteria (KKM) and there are 62.50% of students assessed as not achieving the KKM. In cycle II, based on student learning test results in cycle II, it can be seen that student learning outcomes obtain a mean score of 93.55, where all students get a score > minimum completeness criteria, so 100% of students are declared complete in learning process. From these results, showed a significant increase in learning outcomes from cycle I to cycle II. Thus it can be concluded that the cooperative learning model type Think Pair Share (TPS) can improve student learning outcomes.